Demonstration of Terabit/s LAN-WDM for the Evolution of B5G/6G Fronthaul Networks - Jiao Zhang; Qingsong Wang; Junhao Zhang; Xiang Liu; Bingchang Hua; Jian Chen; Zhigang Xin; Yuancheng Cai; Mingzheng Lei; Yucong Zou; Liang Tian; Guo Zhao; et al. (IEEE Photonics Journal)
Intensity modulation/direct detection (IM/DD) and coherent schemes are two kinds of promising solutions to achieve the evolution for B5G/6G fronthaul networks. IM/DD has more mature commercial deployment applications for short-reach applications with lower costs and simpler configurations compared with coherent solutions. In this article, we experimentally demonstrate a local area network-wavelength division multiplexing (LAN-WDM) IM/DD access system with a record bit rate of 2 Tb/s (250 Gbit/s × 8) probabilistic shaping eight-pulse amplitude modulation (PS-PAM-8) signal with joint equalization techniques to support the evolution of future B5G/6G mobile fronthaul networks. Considering the 20% Soft Decision Forward Error Correction (SD-FEC) threshold with the bit error rate (BER) of 2 × 10−2, we realize a record net bit rate of 1.6 Tb/s over 5 km fiber. This system can potentially support a 12-wavelengths transmission with the total line rate of 3 Tb/s (250 Gbit/s × 12). Moreover, we analyze the challenges of the evolution, usage scenarios, digital signal processing (DSP) implementation, transmission rate and distance, and the tolerance of dispersion with different wavelengths. The LAN-WDM can be considered as a feasible and potential candidate scheme to meet the evolution and deployment of B5G/6G Terabit/s fronthaul networks.